2009
DOI: 10.1523/jneurosci.5451-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Thick Visual Cortex in the Early Blind

Abstract: We investigated the key neurodevelopmental factors that determine cortical thickness, namely synaptogenesis and regression, by analyzing the thickness of the visual cortex in humans with early-and late-onset blindness. The bilateral visual cortices of the early blind were significantly thicker than those of the late blind and the sighted controls, but the latter two groups did not differ significantly. This suggests reduced "pruning" of synapses in the visual cortex, which may be due to a lack of visual experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
160
9
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(198 citation statements)
references
References 44 publications
26
160
9
3
Order By: Relevance
“…It is well established that amblyopia is a failure of the cortical developmental process [45][46][47][48], although the exact extent of the visual cortex deficit is largely unknown. Previous studies have shown that the thickness of visual cortex in blind patients can manifest compensatory thickening [41,49]. The increased thickness of the calcarine sulcus in this study could reflect more visual stimulation in the primary visual cortex, and an increase in connectivity in this region.…”
Section: Discussionsupporting
confidence: 48%
“…It is well established that amblyopia is a failure of the cortical developmental process [45][46][47][48], although the exact extent of the visual cortex deficit is largely unknown. Previous studies have shown that the thickness of visual cortex in blind patients can manifest compensatory thickening [41,49]. The increased thickness of the calcarine sulcus in this study could reflect more visual stimulation in the primary visual cortex, and an increase in connectivity in this region.…”
Section: Discussionsupporting
confidence: 48%
“…One could thus say that it is the input that determines which connection gets pruned and which is left unchanged (Sur et al, 1988;Sharma et al, 2000;von Melchner et al, 2000). If a person lacks visual input, the natural pruning process could be disturbed, leaving exuberant connections, as also indicated by recent findings of increased cortical thickness in the visual cortex of blind volunteers (Jiang et al, 2009). …”
Section: Figurementioning
confidence: 99%
“…This is done to avoid biases across subjects with different curvature. Considering a nominal voxel size of 1.3 -1.5 mm, the voxel size is 70% -80% of the cortical thickness of V1 of 1.8 ± 0.2 mm (Jiang et al, 2009). This resolution is thus insufficient to resolve laminar features, but adequate to estimate the influence of surface vasculature.…”
Section: Surface Detectionmentioning
confidence: 99%